Influence of a physical training program on muscle strength, balance and gait velocity among women with osteoporosis - Aveiro, Mc; Granito, Rn; Navega, Mt [UNESP]; Driusso, P; Oishi, J (Associação Brasileira de Pesquisa e Pós-Graduação em Fisioterapia, 2006)
OBJECTIVES: The trend towards increased life expectancy will certainly lead to increases in morbidity and mortality relating to osteoporosis. Because of the lack of well defined protocols on the intensity and frequency of easily performed physical exercises for Brazilian women, this study proposed to analyze the effects of a training program for ankle muscle strength, balance performance and gait velocity among women with a densitometric diagnosis of osteoporosis. METHODS: Twelve female volunteers (age 68.7 ± 2.7 years) underwent physical evaluation and subsequent reevaluation after twelve weeks. The physical activity program was guided by a physical therapist, who conducted 60-minute sessions, three times a week for twelve weeks. Each training session included some stretching exercises, strengthening exercises for the ankle dorsiflexor and plantar-flexor muscles, with 50% of 10-repetition maximum (10-RM), and balance training. RESULTS: The variables analyzed regarding balance index, gait velocity and muscle strength presented significant improvement (p < 0.05), as shown by the Wilcoxon non-parametric test. CONCLUSION: After the 12-week exercise program, the participants presented benefits in terms of their fitness. The results demonstrate that the training had a role in improving the condition of this group of patients, thus suggesting that this program was effective, easy to implement and safe for Brazilian women with osteoporosis. Therefore, it can be seen that physical activity programs are efficient in improving balance performance, gait velocity and ankle muscle strength among elderly women with osteoporosis.

OBJETIVOS: A tendência de aumento na expectativa de vida certamente representará incrementos na morbidade e na mortalidade em eventos relacionados a osteoporose. Devido à falta de protocolos bem definidos na intensidade e freqüência de exercícios físicos, que sejam fáceis de se realizarem, para mulheres brasileiras, este estudo propôs analisar os efeitos de um programa de treinamento na força muscular do tornozelo, no equilíbrio funcional e na velocidade da marcha de mulheres com diagnóstico densitométrico de osteoporose. MÉTODOS: Doze mulheres voluntárias (idade 68,7 ± 2,7) foram submetidas à avaliação física e, posteriormente, reavaliadas após doze semanas. O programa de atividade física foi orientado por um fisioterapeuta, que trabalhou 60 minutos, 3 vezes por semana, por doze semanas. Cada sessão de treinamento incluiu alguns exercícios de alongamento, fortalecimento muscular dos músculos flexores plantares e dorsiflexores do tornozelo, com 50% de 10-repetições máximas (10-RM) e treino de equilíbrio. RESULTADOS: As variáveis relacionadas ao índice de equilíbrio, à velocidade da marcha e à força muscular apresentaram melhora significativa (p < 0,05), analisadas por meio do teste não paramétrico de Wilcoxon. CONCLUSÃO: Após as doze semanas de treinamento, foram observados benefícios no condicionamento das voluntárias. Os resultados demonstram que o treinamento proposto, teve influência na melhora desse grupo de pacientes, sugerindo que o programa foi efetivo, fácil e seguro para mulheres brasileiras portadoras de osteoporose. Portanto, programas de atividade física são eficientes para melhorar o equilíbrio funcional, a velocidade da marcha e a força muscular do tornozelo de mulheres idosas portadoras de osteoporose.
Influência de um programa de treinamento físico na força muscular, no equilíbrio e na velocidade da marcha de mulheres portadoras de osteoporose
Keywords: balance; physical training; gait velocity; muscle strength; osteoporosis; equilíbrio; treinamento físico; velocidade da marcha; força muscular; osteoporose